A Reversed Inset Toe PIPJ Vascularized Joint Transfer for Finger PIPJ Composite Defect Reconstruction. Issue 1 (January 2021) - Lin, Yu-Te; Loh, Charles Yuen Yung
Abstract : Background: Free vascularized joint transfers (VJT) are indicated for reconstruction of a composite defect of the finger joints. When the bone defect involves the proximal interphalangeal joint (PIPJ) and the full length of the middle phalanx, using the toe PIPJ with a shorter middle phalanx to reconstruct such a defect will be difficult. In this article, we describe an unusual application to repair the composite defect with a reversed inset of the toe PIPJ, where the proximal phalanx of the toe is placed distally and vice versa. Methods: We describe a new technique to repair the composite defect with a reversed inset of the toe PIPJ. A 33-year-old woman sustained a crush injury to the left, middle, and ring finger, having fallen off her moped in a road traffic incident. A vascularized PIPJ from the second toe along with a hemipulp (1 × 4 cm) from the great toe transfer was performed with a reverse inset. Results: With intensive physiotherapy and surgical tenolysis, a range of motion of 20–80 degrees at the new PIPJ was achievable. The joint motion was stable, and the radiograms of the finger demonstrated no visible joint degeneration. She reported the use of the finger, which improved overall hand function. Conclusion: Reverse inset of toe PIPJs is possible in simultaneous reconstruction of damaged finger PIPJs and building up of bony length distally.